Bilateral Germ Cell Tumor of the Testis: Biological and Clinical Implications for a Stem Versus Genetic Origin of Cancers - Jamaal C. Jackson; Darren Sanchez; Aron Y. Joon; Marcos R. Estecio; Andrew C. Johns; Amishi Y. Shah; Matthew Campbell; John F. Ward; Louis L. Pisters; Charles C. Guo; Miao Zhang; Niki M. Zacharias; et al. (Cells)
Germ cell tumors of the testis (GCTs) provide an ideal tumor model to investigate the cellular versus genetic origin of cancers. In this single institutional study, we evaluated 38 patients with bilateral GCT, including tumors that occurred simultaneously (synchronous) and those occurring at different times (metachronous). For nine of these patients, DNA was isolated from the right and left GCT to determine the genomic and epigenetic differences between tissues using whole-exome sequencing (WES) and reduced representation bisulfite sequencing (RRBS). We found that seminomas and non-seminomas are molecularly distinct based on DNA methylation and not due to synchronous or metachronous disease. In addition, we did not observe conservation of genetic mutations in right and left GCT in either synchronous or metachronous disease. Our data suggest a cellular origin for bilateral GCT.